Effects of extension service on the uptake of climate-smart sorghum production practices: insights from drylands of Ethiopia - Gurmu, M.; Sime, M.; Hirpa Tufa, A.; Feleke, S.; Abdoulaye, T. (Elsevier, 2024)
The promotion of climate-resilient practices (CRPs) requires the development of the capacity of farmers to adopt these practices owing to the knowledge-intensive nature of technologies. Extension services serve as a conduit for facilitating the conceptualization of CRPs and are instrumental in improving the resiliency and mitigation of climate change. We used a social-ecological framework and a multivariate probit model to analyze the drivers of the CRP uptake in moisture-stressed areas in Ethiopia, with a particular focus on extension services. Unlike previous studies that investigated a single technology, we considered a bundle of technologies. We focused on the use of two capital-intensive CRPs (drought-resistant seed and inorganic fertilizer) and four knowledge-intensive CRPs (minimum tillage, farmyard manure, water-saving technology, and crop residue retention). The role of extension services in promoting other CRPs beyond input and capital-intensive technologies was insignificant. Heterogeneity analysis revealed that the correlation between extension services and the adoption of other knowledge-intensive natural resource management practices holds irrespective of the proximity to the extension service providers. This finding highlights the need for targeted and tailored interventions that support farmers to address the challenges faced by them in moisture-stressed areas. Accordingly, we propose continuously improving the ability of the extension service providers to promote climate-change adaptation knowledge and practices. This should be accompanied by efforts to strengthen a pluralistic extension system, improve land tenure security, and decrease transaction costs for farmers through output market linkages.